ANALISIS PERBANDINGAN EFEKTIFITAS LENIFF DENGAN IRCS ESM PRODUK INDUSTRI NASIONAL UNTUK SURVEILLANCE KRI - Ardyanzah, Ariza; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
One of the threats in the maritime domain is the threat of electronic warfare. To deal with electronic warfare threats, a good electronic wave detection sensor is needed. The national defense industry has been able to manufacture electronic warfare sensors called LENIFF and IRCS ESM. The two equipments have slightly different features even though they are grouped under electronic warfare sensors. To determine the effectiveness of the two sensors of domestic products in supporting electronic warfare by the KRI, a comparative analysis was carried out using the measurement of effectiveness (MoE) method.